The Microbial Profile and Contaminants of Bubugn, An Ethiopian House Hould Fermented Beverage - Belay, Getnet; Minyamer, Tigist; Masresha, Getinet (The International Journal of Biotechnology, 2018)
Bubugn is a cereal based traditional fermented Ethiopian low alcoholic beverage. It is one of the traditional fermented beverages used for a drink of holidays, wedding ceremony and also used as a source of income. The aims of this study were to determine the microbiology, microbial contaminants and physicochemical characteristics of Bubugn. Nine Samples of Bubugn were collected from Gondar town in three district areas; Azezo (A), Arada (B) and Kebele 18 (C). Microbial counts and physicochemical analysis were enumerated using standard microbiological methods. The mean value of the pH of the samples was 4.20 + 0.14; and the mean value of moisture content was 45. 79 +1.35. The mean crude fat, ash and ethanol contents of Bubugn were 6.67 + 0.16, 4.47+ 0.40 and 1.79 + 0.13, respectively. The mean number of total mesophilic aerobic bacteria, yeasts and molds and lactic acid bacteria of Bubugn were 3.74×105 cfu/ml, 5.68 ×106 cfu/ml and 7.52×105 cfu/ml respectively. Bubugn samples were contaminated by Shigella species, E. coli and S. aureus which could be due to poor hygienic conditions related to washing of preparation material, use of contaminated water and poor personal and domestic hygiene. The collected Bubugn samples were contaminated by different microorganisms and therefore, there should be the development of an advanced technique to improve quality.